A field study on the aerodynamics of freight trains with different stacking configurations. Issue 232 (January 2023) - Quazi, Ariq; Crouch, Timothy; Bell, James; McGreevy, Tony; Thompson, Mark C.; Burton, David
Abstract: A full-scale 48-foot shipping container was instrumented with surface pressure taps and loaded onto a number of single- and double-stacked container freight trains. Surface pressure data enabled the container pressure drag coefficient to be evaluated for a range of different train loading configurations, container positions along the train, and atmospheric wind conditions. Field-based measurements show that for low and high crosswind conditions surface pressure distributions measured on the front face of the instrumented container are in good agreement with those reported in past studies. However, the magnitude of the pressure drag coefficient was found to be typically 50% lower for all loading cases analysed compared with previous seemingly analogous wind-tunnel and numerical investigations. For high crosswind conditions, the drag coefficient was found to increase and correlated well with the level of asymmetry observed in the measured pressure distributions. This was true for all cases regardless of the position along the length of the train. In the absence of direct information of the incident free-stream wind conditions, the level of asymmetry in the pressure distributions was found to provide a viable indirect method for assessing the impact that crosswinds have on the aerodynamic drag of freight trains. Highlights: A full-scale shipping container was instrumented with surface pressure taps. Pressure drag was evaluated for different loading configurations and container locations. Drag coefficient was 50% lower compared with previous investigations. An indirect method for assessing the effect of wind conditions on drag was established. Estimates for aerodynamic efficiency and loading configuration considerations are made.